2020
DOI: 10.3390/jcm9092986
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of COVID-19 Infection in Kidney Transplant Recipients: A Universal Effort to Preserve Patients’ Lives and Allografts

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has posed a significant challenge to physicians and healthcare systems worldwide. Evidence about kidney transplant (KTx) recipients is still limited. A systematic literature review was performed. We included 63 articles published from 1 January until 7 July 2020, reporting on 420 adult KTx recipients with confirmed COVID-19. The mean age of patients was 55 ± 15 years. There was a male predominance (67%). The majority (74%) were deceased donor recipients, and 23%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 95 publications
3
46
0
2
Order By: Relevance
“…In our study population, most patients had at least one immunosuppressive agent withdrawn, with the exception of steroids. A recent systematic review by Marinaki et al [ 14 ], including 420 KTs with COVID-19, reported that reduction/withdrawal of immunosuppression was done in 58% patients and all immunosuppressive agents were maintained in only 5%. In our case, 80.9% of patients were managed with immunosuppression reduction, while 19.1% maintained the complete immunosuppressive regimen ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, most patients had at least one immunosuppressive agent withdrawn, with the exception of steroids. A recent systematic review by Marinaki et al [ 14 ], including 420 KTs with COVID-19, reported that reduction/withdrawal of immunosuppression was done in 58% patients and all immunosuppressive agents were maintained in only 5%. In our case, 80.9% of patients were managed with immunosuppression reduction, while 19.1% maintained the complete immunosuppressive regimen ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the general population, a significantly increased fatality rate in transplanted patients has been described recently [26,27]. However, in a review study on COVID-19 in KTx recipients, the general risk of COVID-19 infection was not elevated, while a higher risk for a more severe course of COVID-19 can be detected, especially in the context of existing comorbidities [28]. Thus, recommendations for increasing activities while maintaining social distance seem advisable to keep up PA levels, and following the stabilization of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The recent published sources contain data on about 400 kidney transplant recipients with confirmed COVID-19 and less than a quarter of them were transplanted no more than one year ago. 2 , 3 , 4 Determining the probability of transmission of COVID-19 during a graft is essential to continuation of the deceased transplantation program during a pandemic. Even a total examination of all potential deceased donors for COVID-19 does not guarantee that they are not infected, because the SARS-CoV-2 rRT-PCR test using throat swab specimens can often result in false negatives due to sampling techniques, viral load of the upper respiratory tract and mutations of the virus gene.…”
Section: Discussionmentioning
confidence: 99%